Well-being in the information society : fruits of respect : 8th International Conference, WIS 2020, Turku, Finland, August 26-27, 2020, Proceedings /: fruits of respect : 8th International Conference, WIS 2020, Turku, Finland, August 26-27, 2020, Proceedings. ([2020]) - Unknown
No abstract available